Analisis Stakeholder Dalam Kebijakan Pembatasan Sosial Berskala Besar (PSBB) Jakarta Periode Tahun 2020 - Meilinda Triana Pangaribuan; Adis Imam Munandar (Jurnal Pemerintahan dan Politik, 2021)
Jakarta as one of the provinces in Indonesia which is considered to have a case of Covid 19 is high. The high number of new cases that occurred in Jakarta leads to Jakarta as the area is top (epicenter) in the spread of Covid 19 in Indonesia. Through the Regulation of the Governor of DKI Jakarat No 33 2020 as the basis for the first time Jakarta impose Restrictions on Large-Scale Social (PSBB), which started on April 10, 2020. The application of the PSBB get a response from all parties, both from the public and other stakeholders. The purpose of this research is to analyze the stakeholders and classify stakeholders based on power and interest to the policy PSBB. The research method used is descriptive research kualitatiif with a source of secondary data refers to information that is gathered from sources that already exist. Based on the results of research that the collaboration of stakeholders (stakeholders) such as the local government of DKI Jakarta, academics, employers, the public, and the media became key to the success of the policy PSBB. Keywords: Covid 19, PSBB, Stakeholder